Business Strategy Development With Business Model Canvas And Value Proposition Canvas (Case Study: Frozen Food Redbox) - Hana Shahila Maharani; Muhammad Iqbal Alamsyah (Green Publisher Indonesia, 2025)
The development and changes in people's lifestyles, especially in Indonesia, show an increasing preference for practical, economical, fast, and delicious food. This encourages increased consumption of food products known as ready to serve, namely fast food that has been cooked and can be stored in various ways, including in the form of frozen processed food. This study aims to evaluate and formulate the Redbox Frozen Food business strategy using the Business Model Canvas (BMC) and Value Proposition Canvas (VPC) approaches. The research method used is qualitative, with data collection through semi-structured interviews with management and customers. Based on the analysis of Value Proposition Canvas (VPC) and Business Model Canvas (BMC), Redbox Frozen Food is considered to have understood consumer needs well, such as practicality, time saving, and ease of serving, and is a solution for small business actors. Redbox also excels in terms of strategic location, competitive prices, and friendly service, although it still faces obstacles in the online ordering system and stock availability. Redbox's business model is quite solid with customer segments including housewives, small business actors, and busy individuals, as well as distribution channels through physical stores, WhatsApp, and marketplaces. Recommended development strategies include strengthening digital services such as automated chatbots, expanding to other marketplace platforms, diversifying the market to student and single worker segments, and implementing digital stock management. To build loyalty, Redbox can also create a membership program and provide educational content.